Co‐Translational Deposition of N6‐Acetyl‐L‐Lysine in Nascent Proteins Contributes to the Acetylome in Mammalian Cells - Dingyuan Guo; Nan Li; Xiaoyan Zhang; Runxin Zhou; Jie He; Xiao‐Ping Ding; Weixing Yu; Fuqiang Tong; Sibi Yin; Yu Wang; Xin Xu; Long Wang; et al. (Advanced Science)
Abstract N6‐acetyl‐L‐lysine residue is abundant in dietary protein but little is known about its potential influences on the diet‐consumers. Herein, it is reported that Lysyl‐tRNA synthetase (KARS) mediates co‐translational deposition of diet‐derived N6‐acetyl‐L‐lysine (AcK) in nascent proteins to contribute to the acetylome in cells. Acetylated dietary protein is a direct source of AcK that can widely and substantially regulate the acetylome in multiple organs of mice. By analyzing the mechanisms underlying AcK contributing to the acetylome in mammalian cells, it is found that KARS can utilize AcK as an alternative substrate to produce N6‐acetyl‐l‐lysyl‐tRNA. The crystal structure of KARS in complex with AcK at 2.26 Å resolution shows that AcK shares the same substrate‐binding pocket as L‐lysine, allowed by a sidechain flip of Tyr499. The generated N6‐acetyl‐L‐lysyl‐tRNA introduces AcK into growing nascent polypeptide and results in protein acetylation, including the regions buried inside folded proteins that are post‐translational modification (PTM)‐inaccessible and functionally important. This undocumented protein modification mechanism is inherently different from PTM and termed as co‐translational modification (coTM). It is expected to extend the repertoire of acetylome and improve the understanding of protein modification mechanisms in cells.